Nihongo module 1 : basic level - Ocdenaria, Jose Marie Elmido; Biscocho, Shiela Pilapil- (Intramuros, Manila : Unlimited Books, 2018)
This book is a useful learning tool and guide of the students in learning the basic knowledge of the Japanese language which is functional in dealing with the Japanese or those who wish to visit the land of the rising sun in the future.
1. Basic Expressions and Greetings -- 2. Self-introduction: easy way -- 3. Numbers: Let's Count -- 4. Date and Time: When is our meeting? What Time? -- 5. Price and Demonstrative Pronouns: how much is that book?-- 6. Simple adjectives: Japan is awesome -- 7. Existential sentences: I have a dream! -- 8. Basic verbs: I want to eat sushi and ramen -- 9. Japanese Characters: Hiragana, Katakana & Basic Kanji.
Includes bibliographical references.
Keywords: JAPANESE LANGUAGE -- ENGLISH